Assessment of untreated and vermifiltration treated pharmaceutical industrial effluent in fish Channa punctata using biochemical, histopathological, ultrastructural and ATR-FTIR analysis - Harpal Kaur; Pooja Chadha (Scientific Reports)
Abstract The unfettered discharge of untreated pharmaceutical effluent into water bodies poses severe menace to aquatic ecosystem. The conventional approaches found to be ineffectual in treating pharmaceutical effluent due to certain issues such as lack of eco-friendliness, cost extensive, also sludge is formed which further increases the expenditure for processing. In context of developing nations, the cost effectiveness and environmental sustainability of vermifiltration technology make it an ideal alternative to conventional wastewater treatment techniques. The current exploration was devised to appraise the effect of untreated and vermifiltration treated effluent in fish Channa punctata through biochemical, histopathological, ultrastructural and ATR-FTIR analysis. Considerably augmented alterations in biochemical parameters (MDA, SOD, CAT and GST) in liver, gill and kidney tissues were scrutinized in untreated group. After 45 days of exposure, 4.35, 4.19 and 3.89 folds hike in MDA content were noticed in liver, gill and kidney tissues of untreated group respectively in contrast to control group. Histopathological examination in fish unveiled to untreated effluent exhibited numerous distortions in liver (necrosis, vacuolization, hepatocyte degeneration), gill (disintegration of primary lamellae, upliftment of gill epithelial layer, fusion of secondary lamellae) and kidney (necrosis, degenerated and constricted glomerulus) tissues. Scanning electron microscopy examination further reiterated the anomalies perceived in histopathological investigation. Further, ATR-FTIR analysis presented more biomolecular alterations in exposed tissues. On contrary, fewer biochemical, histopathological, ultrastructural and biomolecular alterations were noticed in treated effluent exposed fish implies its less toxic nature. The outcomes of the study concluded that vermifiltration technology is trustworthy, economic and sustainable technology for treating different industrial effluents.